Differences Between Patients With Intermittent Claudication and Critical Limb Ischemia Undergoing Endovascular Intervention: Insights From the Excellence in Peripheral Artery Disease Registry. (November 2021) - Patel, Kunal; Liu, Yulun; Etaee, Farshid; Patel, Chirag; Monteleone, Peter; Patel, Mitul; Amer Alaiti, Mohamad; Metzger, Christopher; Banerjee, Avantika; Minniefield, Nicole; Tejani, Ishita; Brilakis, Emmanouil S.; et al.
Abstract : Background: There are limited data on differences in angiographic distribution of peripheral artery disease and endovascular revascularization strategies in patients presenting with intermittent claudication (IC) and critical limb ischemia (CLI). We aimed to compare anatomic features, treatment strategies, and clinical outcomes between patients with IC and CLI undergoing endovascular revascularization. Methods: We examined 3326 patients enrolled in the Excellence in Peripheral Artery Disease registry from 2006 to 2019 who were referred for endovascular intervention for IC (n=1983) or CLI (n=1343). The primary outcome was 1-year major adverse limb events, which included death, repeat target limb revascularization, or target limb amputation. Results: Patients with CLI were older and more likely to have diabetes and chronic kidney disease and less likely to receive optimal medical therapy compared with IC. Patients with IC had higher femoropopliteal artery interventions (IC 87% versus CLI 65%; P <0.001), while below the knee interventions were more frequent in CLI (CLI 47% versus IC 12%; P <0.001). Patients with CLI were more likely to have multilevel peripheral artery disease (CLI 32% versus IC 15%, P <0.001). Patients with IC were predominantly revascularized with stents (IC 48% versus CLI 37%; P <0.001) while balloon angioplasty was more frequent in CLI (CLI 37% versus IC 25%; P <0.001). All-cause mortality was higher in patients with CLI (CLI 4% versus IC 2%; P =0.014). Major adverse limb event rates for patients with IC and CLI were 16% and 26%, respectively ( P <0.001) and remained higher in CLI after multivariable adjustment of baseline risk factors. Conclusions: Patients with IC and CLI have significant anatomic, lesion, and treatment differences with significantly higher mortality and adverse limb outcomes in CLI. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01904851. Abstract : Supplemental Digital Content is available in the text.